Micropatterning of reduced graphene oxide by meniscus-guided printing. (October 2017) - Chang, Won Suk; Jeong, Hwakyung; Kim, Jung Hyun; Lee, Sanghyeon; Wajahat, Muhammad; Han, Joong Tark; Cho, Sung Ho; Seol, Seung Kwon
Abstract: An effective approach is required to improve the spatial resolution and electrical conductivity of printed graphene patterns for advanced graphene-based printed electronics. Here, we describe a simple and effective strategy to fabricate few-micrometer-wide graphene patterns by meniscus-guided printing, using a highly concentrated graphene oxide (GO, 2 wt%) ink. Our approach exploits the rapid solidification of an ink meniscus formed by horizontal pulling of a micronozzle. To achieve uniform printing with continuous flow of the highly concentrated GO ink through the nozzle, polyvinylpyrrolidone (PVP), which acts as a gelation inhibitor and rheology modifier, was added to the aqueous GO solution. GO reduction and PVP removal from the printed patterns was achieved simultaneously, by thermal treatment. Electrical conductivities and widths of the reduced GO (rGO) patterns could be easily modulated by adjusting the nozzle-pulling rate and changing the nozzle-opening size, respectively. Toward applications in electronics, successful fabrication of a field-effect transistor based on a printed rGO channel is also described. This approach can be effective for high-resolution printing of graphene patterns for electronic applications. Graphical abstract: